Kualitas Pedestrian di Kawasan Jalan Pahlawan – Trilomba Juang Kota Semarang dengan Metode Global Walkability Index - Kurnianingtyas, Agnesia Putri; Tamara, Anindya Putri; Rofi'i, Imam (Jurnal Wilayah dan Kota, 2024)
Walkable city is a concept to support livable and sustainable cities. A walkable city is a pedestrian-friendly city where pedestrian spaces and facilities are available in good quality so that they can support the mobility of space users on foot as a form of green mobility. Therefore, it is important to provide a good quality pedestrian to guarantee the safety, comfort and security of people who pass by. This research aims to assess the quality of pedestrians on the Pahlawan road, Pandanaran II road and Tri Lomba Juang road. This area is located in the central area of ​​Semarang city and has high activity, such as government offices, private offices, trade and services, education, and public spaces. The number of users of this space is quite high and some of the users of the space are pedestrians, so it is necessary to assess whether the existing pedestrian area can meet the mobility needs of users or not. Pedestrian quality assessment uses the global walkability index method where there are 9 indicators used as the basis for assessment. The assessment results show that pedestrians on Pahlawan road have a score of 79 (good and adequate). While pedestrians on Pandanaran II road have a score of 57 (fairly good and adequate) and pedestrians on Tri Lomba Juang road have a score of 50 (not good and adequate enough). Keywords: pedestrian, quality, walkability index